Evaluasi Kesiapan Laboratorium Elektronika Kejuruan Menghadapi Industri 4.0: Analisis Fasilitas, Sistem, dan Sumber Daya Manusia - Yudha, Irvan; Rochayati, Umi; Salimah, Zahrotun (invotek, 2025)
This study aims to evaluate the readiness of electronics engineering laboratories in Vocational High Schools (SMK) of Sidoarjo Regency in facing the demands of the Industrial Revolution 4.0. The evaluation focused on four main aspects: laboratory planning, equipment availability, maintenance and management systems, and the competence of laboratory personnel. This study used a descriptive method with a mixed-method approach, involving six vocational schools and respondents from productive teachers, vice principals in the field of infrastructure, and laboratories. Data was obtained through questionnaires, observations, documentation, and in-depth interviews, then analyzed descriptively. The results showed that the average equipment readiness rate was in the "underprepared" category (54.1%), while most schools did not have certified laboratories. Laboratory management is generally still partial and is not systematic, although the usefulness of the laboratory is highly related on by teachers with an average score of 54.4 out of 64. These findings indicated a gap between the availability of facilities, human resource competencies, and the demands of industry-based vocational learning 4.0. The limitations of this study lie in the limited scope of the area and it has not measured the direct impact on student learning outcomes. The practical implications of this study included the importance of strengthening collaboration among schools, industry, and the government in laboratory planning, improving practice facilities, and training and certification of laboratory personnel. Socially, laboratory modernization is an important foundation in producing adaptive and competitive vocational graduates. This study makes an original contribution to mapping the systemic readiness of vocational laboratories in Indonesia.